Most Colletotrichum species associated with tree tomato (Solanum betaceum) and mango (Mangifera indica) crops are not host specific (2017)
An important constraint for crop production in Colombia is the high incidence of anthracnose caused by Colletotrichum species. Even though several studies have focused on understanding these fungi, many questions are still unanswered. One of these questions focuses on the relationship the different fungal species within the genus have with their hosts and whether they displayany host preference or host specificity. In Colombia, diseases caused by Colletotrichum species are particularly severe in mango (Mangifera indica) and tree tomato (Solanum betaceum) crops. In a previous study, the Colletotrichum phylogenetic species attacking these crops were identified. This study aimed to determine whether strains collected from tree tomato and mango showed host preference or host specificity by assessing aggressiveness, spore density, latent period, and fitness of each strain on the two hosts. Strains were collected in the departments of Cundinamarca and Tolima from plants and presented typical anthracnose symptoms. Strains belong to the species C. acutatum, C. asianum, C. boninense, C. gloeosporioides, C. tamarilloi, and C. theobromicola. A conidial suspension was used to inoculate detached leaves as well as whole plants from both hosts. No host preference was found in the strains evaluated and only the C. gloeoporioides strain showed host specificity. However, in general, strains produced a higher spore density when inoculated on the alternate host. This might be an indication of the difference in the degree of adaptation to each host. Also, statistical analysis revealed that strains use different infection strategies, as defined by the values in the assessed parameters, when infecting each host. The implications of using quantitative estimations of fitness when studying fungal pathogens in light of the results, are discussed